1988
DOI: 10.3109/00365528809093890
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Overweight to Hiatus Hernia and Reflux Oesophagitis

Abstract: In a prospective study in 1224 patients referred for upper alimentary endoscopy, reflux oesophagitis was found in 195 (16%) of the patients and hiatus hernia in 249 (20%). In patients with reflux oesophagitis a coexisting hiatus hernia was found in 68%. The weight-for-height index (W/H1.8), which expresses the degree of overweight, was significantly higher both in patients with hiatus hernia and in the patients with reflux oesophagitis, indicating an overweight of approximately 5% in both groups. The overweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 8 publications
6
65
1
4
Order By: Relevance
“…This is different from some studies showing that adjustment for GERD causes the attenuation or disappearance of the effect of increased BMI on BE risk [9,52], but it agrees with other studies showing that this adjustment does not affect the association [40,49,53]. Although obesity is a well-recognized risk factor for GERD through mechanically induced reflux by enhancing the intra-abdominal pressure [54] or facilitating the formation of a hiatal hernia [55,56], a slightly overweight status with a BMI of 23.0-24.9 might be insufficient to provoke induced reflux. Supporting this, a recent study demonstrated that, although esophageal acid exposure increased significantly with increasing BMI, the most remarkable increase in acid reflux occurred in the BMI zone of 25-30 [57].…”
Section: Discussioncontrasting
confidence: 37%
“…This is different from some studies showing that adjustment for GERD causes the attenuation or disappearance of the effect of increased BMI on BE risk [9,52], but it agrees with other studies showing that this adjustment does not affect the association [40,49,53]. Although obesity is a well-recognized risk factor for GERD through mechanically induced reflux by enhancing the intra-abdominal pressure [54] or facilitating the formation of a hiatal hernia [55,56], a slightly overweight status with a BMI of 23.0-24.9 might be insufficient to provoke induced reflux. Supporting this, a recent study demonstrated that, although esophageal acid exposure increased significantly with increasing BMI, the most remarkable increase in acid reflux occurred in the BMI zone of 25-30 [57].…”
Section: Discussioncontrasting
confidence: 37%
“…Our study is consistent with one study conducted by Arvind Kumar et al [42], indicated that there was significant association between 31 to 40 year age group and Dyspepsia. On the other hand, in studies conducted in Shiraz [14] and US [45], there was no relationship between age and Dyspepsia, while other studies found the positive and reverse associations between age and functional Dyspepsia, respectively [44,46].…”
Section: Discussionmentioning
confidence: 89%
“…The mechanisms by which obesity increases the risk of oesophageal adenocarcinoma remain open for discussion but may be linked to the predisposition of obese individuals to gastro-oesophageal reflux, hiatal hernia and consequent Barrett's oesophagus. [7][8][9][10][11]18,19 Obesity has increased in most developed countries and is gradually affecting developing countries as well. Central obesity, the type of obesity likely to be involved in the postulated pathogenic process, is particularly common among men, though no adequate information is available on type of obesity and oesophageal adenocarcinoma risk.…”
Section: The Hypothesismentioning
confidence: 99%